Metacognitive training pada pasien dengan skizofrenia: A literature review - Amira, Iceu; Hendrawati, Hendrawati; Maulana, Indra; Platini, Hesti (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: Schizophrenia is a psychotic disorder characterized by major disturbances in thoughts and emotions. Patients with schizophrenic disorders have disturbances in cognitive function characterized by disturbances in the cognitive system, so metacognitive training therapy is needed. Metacognitive Training Therapy is a combination of psychoeducation, cognitive remediation therapy and cognitive behavioral therapy aimed at reducing the overall severity of symptoms and improving several neurocognitive subdomains and social cognitive functions.Purpose: This study aims to identify metacognitive training interventions in patients with schizophrenia.Method: The databases used were EBSCOhost (Cinahl) and Pubmed and 159 articles were found.Results: Stage through the initial selection obtained 32 articles. Then, articles were selected based on inclusion criteria in the form of publications in the last 10 years (2013-2023), national and international journals in Indonesian and English, articles with full text, and 5 peer-reviewed articles. Next, articles were selected based on research title, country, research objectives, research methods, population and sample, and research results.Conclusion: This study found that participants who had quite severe symptoms at the start of training were greatly helped in reducing the overall severity of symptoms by the metacognitive therapy they underwent.Keywords: Metacognitive; Schizophrenia; Training.Pendahuluan: Skizofrenia merupakan gangguan psikotik yang ditandai dengan gangguan utama dalam pikiran dan emosi. Pada pasien dengan gangguan skizofrenia memiliki gangguan dalam fungsi kognitif ditandai dengan adanya gangguan sistem kognitif sehingga diperlukan terapi Metacognitive Training. Terapi Metakognitif Training merupakan gabungan dari psikoedukasi, terapi remediasi kognitif dan terapi kognitif perilaku bertujuan untuk menurunkan keparahan gejala secara keseluruhan serta memperbaiki beberapa subdomain neurokognitif dan fungsi kognitif sosial.Tujuan: Penelitian ini bertujuan untuk mengidentifikasi intevensi metacognitive training pada pasien dengan skizofrenia.Metode: Database yang dilakukan adalah EBSCOhost (Cinahl) dan Pubmed dan ditemukan sebanyak 159 artikel.Hasil: Tahap melalui seleksi awal diperoleh 32 artikel. Kemudian, artikel diseleksi berdasarkan kriteria inklusi berupa terbit 10 tahun terakhir (2013-2023), jurnal nasional maupun internasional yang berbahasa Indonesia dan Inggris, artikel dengan full text, dan artikel yang peer reviewed didapatkan sebanyak 5 artikel. Selanjutnya, artikel diseleksi berdasarkan judul penelitian, negara, tujuan penelitian, metode penelitian, populasi dan sampel, dan hasil penelitian.Simpulan: Penelitian ini menemukan bahwa peserta yang memiliki gejala-gejala yang cukup parah pada awal pelatihan sangat dibantu dalam menurunkan keparahan gejala secara keseluruhan oleh terapi metakognitif yang dijalani.